Assessment of Preparedness Regarding Disaster Management Among Nurses - Kanwal, Rani Saba; Saleem, Sonia; Saleem, Rimsha; Nouman, Adeel (Biological and Clinical Sciences Research Journal, 2025)
Nurses are pivotal in disaster preparedness and response, especially in tertiary care settings where timely and effective intervention is critical. Evaluating their readiness is essential to developing targeted strategies for emergency preparedness. Objective: To assess the preparedness of tertiary care nurses regarding disaster management. Methods: A cross-sectional study was conducted at the Nursing Department of Medicare Hospital, Multan, from February 2024 to February 2025. A total of 100 registered nurses employed permanently at the hospital were enrolled. Data were collected using a structured questionnaire based on a modified version of the Disaster Preparedness Evaluation Tool, comprising 46 items rated on a six-point Likert scale (1 = strongly disagree to 6 = strongly agree). The tool assessed three core dimensions: knowledge, mitigation, response, and evaluation. Statistical analysis was performed using SPSS version 25, and p ≤ 0.05 was considered significant. Results: The study found that prior training did not significantly improve disaster preparedness knowledge (p = 0.783) or evaluation (p = 0.293). However, training was significantly associated with enhanced emergency response skills (p = 0.027). The inter-dimension correlation coefficient was high (r = 0.92), indicating internal consistency. The mean score for the 25 items related to general knowledge, management skills, and family preparedness was 3.08. The score for 15 items on patient-related knowledge and skills was 2.49, while the score for the six items related to evaluation was 2.50. Conclusion: The study revealed inadequate disaster preparedness among tertiary care nurses, despite the region’s vulnerability to natural disasters. Continuous education and hands-on training programs are necessary to enhance their readiness and response capabilities.